Pengaruh Faktor Pengembangan Destinasi Wisata Terhadap Minat Berwisata Halal di Kota Jambi - Nurrokhim; Titin Agustin Nengsih; M. Taufik Ridho (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Tourism is one of the important sectors for the government to improve the economy of a region. Currently, the development of halal tourism is considered to be a very potential tourism sector development both in socio-economic and cultural conditions for an area or region that indirectly feels the impact both social and economic. Jambi City has many tourist attractions and none of them have officially become halal tourist destinations, to achieve this it is necessary to develop tourist destinations and support from various parties including tourists with an interest in travelling halal. Travel interest is closely related to the state of tourist destinations, both in terms of attractiveness, facilities and access to tourist attractions. Therefore, this study aims to determine and analyse the effect of attraction, amenity and accessibility factors on interest in halal tourism in Jambi City. This study uses a quantitative approach, the data used is primary data obtained through distributing questionnaires, observations, interviews as well as documentation. The number of samples in this study were 384 people using non probability sampling with purposive sampling method technique. The results showed that attractions had a positive and significant effect on interest in halal tourism in Jambi City. Amenity shows that there is a significant positive effect on interest in halal tourism in Jambi City. Accessibility shows that there is a significant positive effect on interest in halal tourism in Jambi City. Attractions, amenity, and accessibility together have a significant effect on interest in halal tourism in Jambi City. This study shows that the contribution of the independent variable to the dependent variable is 67.9% and 32.1% is influenced by other factors that are not part of this study.